Genome-wide identification of cis DNA methylation quantitative trait loci in three Southeast Asian Populations. Issue 7 (6th February 2021) - Kassam, Irfahan; Tan, Sili; Gan, Fei Fei; Saw, Woei-Yuh; Tan, Linda Wei-Lin; Moong, Don Kyin Nwe; Soong, Richie; Teo, Yik-Ying; Loh, Marie
Abstract: DNA methylation (DNAm) is an epigenetic modification that acts to regulate gene transcription, is essential for cellular processes and plays an important role in complex traits and disease. Variation in DNAm levels is influenced by both genetic and environmental factors. Several studies have examined the extent to which common genetic variation influences DNAm (i.e. mQTLs), however, an improved understanding of mQTLs across diverse human populations is needed to increase their utility in integrative genomic studies in order to further our understanding of complex trait and disease biology. Here, we systematically examine cis -mQTLs in three Southeast Asian populations in the Singapore Integrative Omics (iOmics) Study, comprised of Chinese ( n  = 93), Indians ( n  = 83) and Malays ( n  = 78). A total of 24 851 cis -mQTL probes were associated with at least one SNP in meta- and ethnicity-specific analyses at a stringent significance level. These cis -mQTL probes show significant differences in local SNP heritability between the ethnicities, enrichment in functionally relevant regions using data from the Roadmap Epigenomics Mapping Consortium and are associated with nearby genes and complex traits due to pleiotropy. Importantly, DNAm prediction performance and the replication of cis -mQTLs both within iOmics and between two independent mQTL studies in European and Bangladeshi individuals is best when the genetic distance between the ethnicities is small, with differences in cis -mQTLs likely due to differences in allele frequency and linkage disequilibrium. This study highlights the importance of, and opportunities from, extending investigation of the genetic control of DNAm to Southeast Asian populations.